2021
DOI: 10.3390/ijms222111749
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Autophagy-Related Gene 2 (ATG2) Results in Accelerated Senescence and Enhanced Immunity in Soybean

Abstract: Autophagy plays a critical role in nutrient recycling and stress adaptations. However, the role of autophagy has not been extensively investigated in crop plants. In this study, soybean autophagy-related gene 2 (GmATG2) was silenced, using virus-induced silencing (VIGS) mediated by Bean pod mottle virus (BPMV). An accelerated senescence phenotype was exclusively observed for the GmATG2-silenced plants under dark conditions. In addition, significantly increased accumulation of both ROS and SA as well as a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Through BPMV-VIGS silencing approach, we successfully identified both positive and negative regulators of defense responses in soybean [20][21][22][23][24][25]. Using the same strategy, we found that when Glyma.18g246400 was silenced, a significantly stunted stature (Figure 1A) and spontaneous cell death on the systemic leaves were observed for the silenced plants (Figure 1B).…”
Section: Silencing Glyma18g246400 Results In Stunted Stature and Spon...mentioning
confidence: 94%
See 3 more Smart Citations
“…Through BPMV-VIGS silencing approach, we successfully identified both positive and negative regulators of defense responses in soybean [20][21][22][23][24][25]. Using the same strategy, we found that when Glyma.18g246400 was silenced, a significantly stunted stature (Figure 1A) and spontaneous cell death on the systemic leaves were observed for the silenced plants (Figure 1B).…”
Section: Silencing Glyma18g246400 Results In Stunted Stature and Spon...mentioning
confidence: 94%
“…Activated defense responses are usually correlated with enhanced disease resistance [20][21][22][23][24][25]. To examine whether disease resistance is enhanced in GmBIR1-silenced plants, SMV strain N tagged with the GUS marker protein (SMV-N-GUS) [33] was inoculated via biolistic bombardment onto three individual leaves collected from both the vector control plants and the GmBIR1-silenced plants.…”
Section: Silencing Gmbir1 Enhances Resistance Against Smv and Pseudom...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, bacteria and viruses can also be degraded in the infected cells through this process [ 70 ]. Autophagy takes place in all life stages of the plant, including development, senescence, and cell death [ 12 , 71 ]. Under normal development and growth conditions, the insensitivity of autophagy is relatively low—basal.…”
Section: Autophagy Contribution To Cell Deathmentioning
confidence: 99%